Factors That Help and Hinder the Implementation of Digital Depression Prevention Programs: School-Based Cross-sectional Study - Joanne R Beames; Lara Johnston; Bridianne O'Dea; Michelle Torok; Helen Christensen; Katherine M Boydell; Aliza Werner-Seidler (JMIR Publications, 2021)
BackgroundDigital prevention programs that are delivered in a school environment can inoculate young people against depression. However, little is known about the school-based factors that help and hinder the implementation of these programs. Staff members are integral for supporting mental health programs in schools and are likely to have a wealth of expertise and knowledge about the factors that affect implementation. ObjectiveThe primary objective of this study was to explore the barriers and facilitators to implementing a digital depression prevention program in Australian secondary schools with teachers, counselors, and principals. The secondary objective was to explore variations in these factors across different school contexts, including the school type (government or nongovernment), location (capital city, regional/or rural areas), and socioeconomic status (SES) (low, medium, high). MethodsThis quantitative cross-sectional survey study assessed the barriers and facilitators to implementing a hypothetical digital prevention program in Australian schools. The survey was taken by 97 teachers (average age 38.3 years), 93 counselors (average age 39.5 years), and 11 principals (average age 50.9 years) across Australia between November 2017 and July 2018. ResultsA range of barriers and facilitators relating to logistics and resources, staff support, and program factors were endorsed by the surveyed staff. Consistent with prior research, common barriers included a lack of time and resources (ie, staff and rooms). These barriers were particularly evident in government, rural/regional, and low socioeconomic schools. Other barriers were specific to digital delivery, including privacy issues and a lack of clarity around staff roles and responsibilities. Facilitators included upskilling staff through training, embedding the program into the curriculum, and other program factors including universal delivery, screening of students' mental health, and clear referral pathways. Knowledge about the program efficacy was also perceived as important by a large proportion of the respondents. ConclusionsThe digital depression prevention program was perceived as suitable for use within different schools in Australia, although certain factors need to be considered to enable effective implementation. Logistics and resources, support, and program factors were identified as particularly important for school-based implementation. To maximize the effectiveness in delivering digital programs, implementation may need to be tailored to the staff roles and school types.